Performance evaluation of 50MWp solar plant under different climatic conditions - Mohamed Saleck Heyine; Ahmed Mohamed Yahya; Daha Hassan Daher; Léon Gaillard; Christophe Menezo; Abdel Kader Mahmoud (Institute of Advanced Engineering and Science, 2022)
The aim of this study was to evaluate a performance analysis of a 50 MWp solar plant connected to the medium voltage electrical grid installed in the Saharan environment of Nouakchott, Mauritania. This study is done in two seasons characterizing the climate of Nouakchott, then in three typical days based on the measurement data that are obtained from the site of the installation. The measurements were collected daily, to improve the performance evaluation, real-time measurements with a step of 10 seconds for solar irradiation, ambient temperature, module temperature, wind speed, and electrical parameters. The performance evaluation was done based on the IEC 61724 standard to study the comportment of the power plant during different weather conditions. The total energy produced by the plant in May 2020 dry season is 10.559 GWh. However, the total energy produced in November 2019 wet season was 8.132 GWh. Besides, the energy injected by the plant into the grid was for a clear day 263.87 MWh, while for a cloudy day was 118.41 MWh, while it was 39.81 MWh for a sandstorm day. The results showed that temperature and irradiation play an important role in the performance of the system.